Administrator danych w polskich parkach narodowych (wybrane aspekty prawno-administracyjne) - Dobkowski, Jarosław; Goerick, Jakub (Studia Prawnoustrojowe, 2019)
The article presents an outline of the problem of determining personal data administrator in the public sphere on the example of one of the forms of nature protection in Poland – national parks. The research focused on the differences between legal defnitions of a data controller that has an essential impact on the process of separating a data controller in a national park. The whole is fnished with de lege ferenda postulates, which would solve this problem.